2021
DOI: 10.1038/s41443-020-00405-4
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in patients with anxiety disorders: a systematic review

Abstract: Men with anxiety disorders have been identified as high risk of developing erectile dysfunction (ED). The aim of this review is to define the prevalence and severity of ED in the male anxiety disorder population. A literature search of three electronic databases (PubMed, Embase and PsychINFO) and a grey literature registry was conducted. Inclusion criteria were studies that investigated adult males, documented diagnosis of anxiety disorders made by a qualified psychiatrist and use of a validated tool to diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 39 publications
(65 reference statements)
0
20
0
Order By: Relevance
“…The strong psychological association between fertility and sexuality is also highlighted by an interview study by Frederick et al, in which more than half of the included male childhood cancer survivors spontaneously expressed concerns about their fertility when asked about their sexual function [15]. Other studies found a higher incidence of male sexual dysfunction in patients suffering of anxiety disorders, in particular post-traumatic stress disorder (PTSD) [24][25][26][27]. Cancer has lately been recognized as one possible stressor inducing PTSD, with a prevalence of PTSD between 7 and 75% among cancer patients [28][29][30][31].…”
Section: Discussionmentioning
confidence: 96%
“…The strong psychological association between fertility and sexuality is also highlighted by an interview study by Frederick et al, in which more than half of the included male childhood cancer survivors spontaneously expressed concerns about their fertility when asked about their sexual function [15]. Other studies found a higher incidence of male sexual dysfunction in patients suffering of anxiety disorders, in particular post-traumatic stress disorder (PTSD) [24][25][26][27]. Cancer has lately been recognized as one possible stressor inducing PTSD, with a prevalence of PTSD between 7 and 75% among cancer patients [28][29][30][31].…”
Section: Discussionmentioning
confidence: 96%
“…Similar to mood, anxiety and reproductive health are closely related, with anxiety an established trigger for sexual dysfunction ( 95 ). However, unlike the experimental evidence revealing an unambiguous and positive modulatory effect for kisspeptin-signalling in depression, its influence on anxiety-like behaviour remains to be fully clarified.…”
Section: Mood and Emotionsmentioning
confidence: 99%
“…Through interviews, we know that people are affected by anxiety at home and the reasons for anxiety are often due to the quarrel of minor matters or the nagging of spouses. [ 27 ] In public situations, people often do not have anxiety in the face of the same things. According to relevant surveys, people are often relaxed when they are at home.…”
Section: Exploring the Reasons Why People Are More Likely To Spread Anxiety At Homementioning
confidence: 99%